Impact of the Specific Extraction-Site Location on the Risk of Incisional Hernia After Laparoscopic Colorectal Resection. Issue 8 (August 2016) - Benlice, Cigdem; Stocchi, Luca; Costedio, Meagan M.; Gorgun, Emre; Kessler, Hermann
Abstract : BACKGROUND: The impact of the specific incision used for specimen extraction during laparoscopic colorectal surgery on incisional hernia rates relative to other contributing factors remains unclear. OBJECTIVE: This study aimed to assess the relationship between extraction-site location and incisional hernia after laparoscopic colorectal surgery. DESIGN: This was a retrospective cohort study (January 2000 through December 2011). SETTINGS: The study was conducted at a high-volume, specialized colorectal surgery department. PATIENTS: All of the patients undergoing elective laparoscopic colorectal resection were identified from our prospectively maintained institutional database. MAIN OUTCOME MEASURES: Extraction-site and port-site incisional hernias clinically detected by physician or detected on CT scan were collected. Converted cases, defined as the use of a midline incision to perform the operation, were kept in the intent-to-treat analysis. Specific extraction-site groups were compared, and other relevant factors associated with incisional hernia rates were also evaluated with univariate and multivariate analyses. RESULTS: A total of 2148 patients (54.0% with abdominal and 46.0% with pelvic operations) with a mean age of 51.7 ± 18.2 years (52% women) were reviewed. Used extraction sites were infraumbilical midline (23.7%), stoma site/right or left lower quadrant (15%), periumbilical midline (22.5%), and Pfannenstiel (29.6%) and midline converted (9.2%). Overall crude extraction site incisional hernia rate during a mean follow-up of 5.9 ± 3.0 years was 7.2% (n = 155). Extraction-site incisional hernia crude rates were highest after periumbilical midline (12.6%) and a midline incision used for conversion to open surgery (12.0%). Independent factors associated with extraction-site incisional hernia were any extraction sites compared with Pfannenstiel (periumbilical midline HR = 12.7; midline converted HR = 13.1; stoma site HR = 28.4; p < 0.001 for each), increased BMI (HR = 1.23; p = 0.002), synchronous port-site hernias (HR = 3.66; p < 0.001), and postoperative superficial surgical-site infection (HR = 2.11; p < 0.001). LIMITATIONS: This study was limited by its retrospective nature, incisional hernia diagnoses based on clinical examination, and heterogeneous surgical population. CONCLUSIONS: Preferential extraction sites to minimize incisional hernia rates should be Pfannenstiel or incisions off the midline. Midline incisions should be avoided when possible.